An analysis of partial efficiencies of energy utilisation of different macronutrients by barramundi (Lates calcarifer) shows that starch restricts protein utilisation in carnivorous fish. Issue 4 (14th March 2017) - Glencross, Brett D.; Blyth, David; Bourne, Nicholas; Cheers, Susan; Irvin, Simon; Wade, Nicholas M.
Abstract: This study examined the effect of including different dietary proportions of starch, protein and lipid, in diets balanced for digestible energy, on the utilisation efficiencies of dietary energy by barramundi ( Lates calcarifer ). Each diet was fed at one of three ration levels (satiety, 80 % of initial satiety and 60 % of initial satiety) for a 42-d period. Fish performance measures (weight gain, feed intake and feed conversion ratio) were all affected by dietary energy source. The efficiency of energy utilisation was significantly reduced in fish fed the starch diet relative to the other diets, but there were no significant effects between the other macronutrients. This reduction in efficiency of utilisation was derived from a multifactorial change in both protein and lipid utilisation. The rate of protein utilisation deteriorated as the amount of starch included in the diet increased. Lipid utilisation was most dramatically affected by inclusion levels of lipid in the diet, with diets low in lipid producing component lipid utilisation rates well above 1·3, which indicates substantial lipid synthesis from other energy sources. However, the energetic cost of lipid gain was as low as 0·65 kJ per kJ of lipid deposited, indicating that barramundi very efficiently store energy in the form of lipid, particularly from dietary starch energy. This study defines how the utilisation efficiency of dietary digestible energy by barramundi is influenced by the macronutrient source providing that energy, and that the inclusion of starch causes problems with protein utilisation in this species.